Probably not : future prediction using probability and statistical inference - Dworsky, Lawrence N., 1943- (Hoboken, NJ : Wiley, 2020)
An introduction to probability and statistics at an introductory level.
Introduction -- An introduction to probability -- Probability distribution functions and some math basics -- Building a bell -- Random walks -- Life insurance -- The binomial theorem -- Pseudorandom numbers and Monte-Carlo simulations -- Some gambling games in detail -- Scheduling and waiting -- Combined and conditional probabilities -- Bayesian statistics -- Estimation problems -- Paradoxes -- Benford's law -- Networks, infectious diseases and chain letters -- Introduction to frequentist statistical inference -- Statistical mechanics and thermodynamics -- Chaos and quanta -- Appendix.
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Prediction theory; Probabilities -- Problems, exercises, etc; Mathematical statistics -- Problems, exercises, etc; Mathematical statistics; Prediction theory; Probabilities; Electronic books; Problems and exercises